Host relations of Kalaharituber pfeilii (Henn.) Trappe & Kagan-Zur - Ntshakaza, Pamella (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2014)
Kalaharituber pfeilii (Henn.) Trappe & Kagan-Zur commonly known as the "Kalahari truffle" is a desert truffle species identified from the Kalahari region of southern Africa. Two other species, Eremiomyces echinulatus (Trappe & Marasas) Trappe & Kagan-Zur and Mattirolomyces austroafricanus (Trappe & Marasas) Trappe & Kovacs are also known to occur in other parts of southern Africa. Truffles are hypogeous fruiting bodies of Ascomycetes, important to humans for their nutritional value and medicinal characteristics. These truffles are known as desert truffles as they prefer to occur under arid or semi-arid conditions characteristic of deserts. Truffle development depends on the presence of a mycorrhizal host, associated microorganisms as well as soil and climatic characteristics. It has been suggested that K. pfeilii has a suspected broad plant host range which includes herbaceous to woody trees and shrubs. However, these relationships have not been verified. Indigenous people of the Kalahari believe that truffles are found under grasses. In the Kalahari, truffle fruiting bodies are often found entangled in Stipagrostis ciliata (Desf.) De Winter var. capensis (Trin. & Rupr.) De Winter roots. S. ciliata, also known as the tall bushman-grass, is the most common grass found in the Kalahari. The objective of this study was to provide conclusive evidence that S. ciliata var. capensis is a host of the Kalahari truffle. Truffle fruiting bodies and grass roots from where the truffles were found were collected from Upington, South Africa. The fruiting bodies were identified by observing their morphological characteristics using the 'Keys of Truffle genera'. All observed physical properties were similar to those of K. pfeilii and further identification was done using molecular techniques. DNA was extracted from the fruiting bodies, mycelial cultures, rhizosheaths and from the S. ciliata var. capensis grass roots, which were then amplified using the specific K. pfeilii specific primers TPF3 and TPR1 and sequenced. The obtained sequence results confirmed that the collected fruiting bodies were those of the K. pfeilii and the molecular techniques also confirmed that K. pfeilii DNA was present in the S. ciliata var. capensis rhizosheath and root cells. Microscopy showed an ectendomycorrhizal association between K. pfeilii and S. ciliata var. capensis. Mycorrhizal resynthesis experiments were conducted to establish this mycorrhizal association in-vitro. They were unsuccessful because of the structure of the grass and the availability of contaminants. And more...
Keywords: Ascomycetes -- Kalahari Desert; Medicinal plants -- Kalahari Desert; Edible fungi -- Kalahari Desert; Truffles -- Kalahari Desert; Desert plants -- Kalahari Desert; Mycorrhizas -- Kalahari Desert; Stipa -- Kalahari Desert